Efficiency Analysis of Technological Methods for Reduction of NOx Emissions while Burning Hydrocarbon Fuels in Heat and Power Plants - S. M. Kabishov; I. A. Trusova; P. E. Ratnikov; D. V. Mendelev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains a comparative efficiency analysis pertaining to application of existing technological methods for suppression of nitric oxide formation in heating boilers of heat generators. A special attention has been given to investigation of NOx  emission reduction while burning hydrocarbon fuel with the help of oxygen-enriched air. The calculations have demonstrated that while enriching oxidizer with the help of oxygen up to 50 % (by volume) it is possible to reduce volume of NOx formation (while burning fuel unit) by 21 %.